Sustained improvement of gas exchange and lung mechanics by vaporized perfluorocarbon inhalation in piglet acute lung injury model. (26th November 2013) - Wang, Xiaoguang; Zhang, Jianpeng; Li, Xiaoling; Liu, Youning; Yang, Haibo; Zhao, Xiaowei; Xie, Lixin; Yin, Lihua
Abstract Introduction New methods for perfluorocarbon (PFC) application have been proposed which include aerosolization and vaporization. However, the experimental documentation of efficacy of vaporization of PFC in the treatment of acute respiratory distress syndrome (ARDS) is still lacking. Objectives This study aims to examine the effects of vaporized PFC on gas exchange and lung mechanics in a piglet model with ARDS. Methods Lung injury was induced in 16 piglets by infusing detergent through tracheal intubation. Eight piglets were treated with vaporized PFC for 2 h followed by 6 h of volume‐controlled ventilation. Another eight piglets receiving 8 h volume‐controlled ventilation were used as controls. Blood gases, lung mechanical and hemodynamic parameters were measured. Results Vaporized PFC treatment significantly increased oxygenation index (P/F ratio) and static lung compliance (Cst) 2 h after therapy compared with the control group (P < 0.05). The P/F ratio reached a peak 5.5 h after the therapy and remained at an increased level for at least 6 h compared with the control group (P < 0.001). Additionally, 6 h post treatment, peak inspiratory pressure was significantly reduced in PFC group when compared with the control group (P < 0.05), and Cst was significantly higher in the PFC group than in the control group (P = 0.001). Conclusions Inhalation of vaporized PFC results in sustained improvement of pulmonary gas exchange and lung mechanics in a detergent‐induced animal model of lung injury. Therefore, the non‐invasive vaporization application technique would be a reasonable alternative to administer perfluorocarbons in severe lung injury.